200 UMP associates join Khatam al Quran and World QuranHour - Nor Salwana, Mohammad Idris (UMPSA, 2023)
KUANTAN, April 13, 2023 - A total of 150 Universiti Malaysia Pahang (UMP) staff and students participated in the Khatam al-Quran and World #QuranHour Ceremony in a programme that took place at the UMP Mosque, Gambang Campus.